THE IMPACT OF COMBINATION OF ROLLING AND OKETANI MASSAGE ON PROLACTIN LEVEL AND BREAST MILK PRODUCTION IN POST-CESAREAN SECTION MOTHERS - Nia Dwi Yuliati; Hadi Hadi; Sri Rahayu; Noor Pramono; Donny Kristanto Mulyantoro (Belitung Raya Foundation, Indonesia, 2017)
Background: Normal childbirth or cesarean section has an effect on the initiation of early breastfeeding. Thus, rolling massage and oketani massage are considered helpful for milk production. However, little is known about the combination of rolling and oketani massage. Objective: To examine the effect of combination of rolling and oketani massage on the levels of prolactin and milk production in post-caesarian section mothers. Methods: A quasi-experimental study with pretest-posttest control group design. Thirty-six samples were selected using consecutive sampling, with 18 each assigned to an experiment and control group. Breast milk production was measured based on the baby's weight, while prolactin levels were measured using ELISA method. Data were analyzed using univariate and bivariate analysis. Results: Results showed that there was a statistically significant difference of prolactin levels after intervention in the experiment and control group with p-value 0.035 (<0.005), and significant difference in breast milk production in both groups in posttest 1 and posttest 2 with p-value 0.000 (<0.05). Conclusion: There was statistically significant effect of the combination of rolling and oketani massage on the increase of prolactin levels and breast milk production. It is suggested that this intervention can be applied in midwifery care in post-cesarean section mothers.